Preliminary Study of Bioluminescence Species in the SouthernBay of Bengal - Wimalasiri, H.B.U.G.M.; Jinadasa, S.U.P.; Dissanayake, D.C.T.; Weidemann, A.; Wijesekera, H. (Proceeding of the 6th Research symposium of Uva Wellassa University, January, 28-29 2016, 2016)
Attached

Marine organis ms ranging from bacteria to fish make their own chemically induced light called bioluminescence, it . is used to hunt, frighten predators, attract mates, communicate, or camouflage than. The bioluminescence phenomenon was studied in the southern Bay of Bengal during August 2015 onboard R/V Roger Revelle operating from Colombo, Sri Lanka. The intensity of light produced by bioluminescem e spices was measured using Recoverable Bathy Photometer (RBP). The RBP recorded light intensity while free falling at a speed o f about 1-1.5 m/s. Several RBP profiles in the upper 200 m were collectedat six different sites encompassing i region 5 - 8N, 85.5 v 88.5E. All samples were collected in the night time to minimi ze interferences from other light sources. Zooplankton samples were collected using 150 pm mesh size plankton net from each location to identify light producing zoo>lankton species. The RBP measurements showed the existence of bioluminescem organisms in all the sampling locations and high light intensity was found up to 150-200 m water depths. Sapphirina sp belonging to the family f phylum Arthropoda was identified as one of the light emitting ies. Studies are underway to examine the luminous substances, and tial distribution of these species, especially around Sri Tankan Sapphirinidae zooplankton s] vertical and coastal waters
Keywords: Bioluminescence; Recoverable bathy photometer; Zooplankton; Bay of Bengal.